Entangled paths towards modernity : contextualizing socialism and nationalism in the Balkans - Dimou, Augusta (Central European University Press, 2009)
The book is a study in comparative intellectual history and discusses how socialist ideology emerged as an option of political modernity in the Balkans of the late nineteenth and early twentieth century. Focusing on how technologies of ideological transfer and adaptation work, the book examines the introduction and contextualization of international socialist paradigms in the Southeast European periphery. At its core is the presentation of three case studies (Serbia, Bulgaria and Greece), intertwined at times through similar, but also divergent paths. Each case aspires to tell a different and yet complementary story with respect to the issue of modernity and socialism. The book analyses the introduction of socialism against the background and in conjunction to other prominent options of political modernity such as nationalism, liberalism and agrarianism.